Enabling mothers through improving mental health literacy and parenting skills - Haleh Heizomi; Mohammad Asgharijafarabadi; Hamid Allahverdipour (BioSocial Health Journal)
Introduction: Mothers often lack insight into their influence on the mental health of their children and may not possess adequate mental health literacy and parenting skills. This study aimed to explore the impact of mental health literacy and parenting skills on the effectiveness of mental health promotion programs for mothers. Methods: A quasi-experimental design was employed in Tabriz, Iran, with two groups – a control group and an intervention group – each comprising 126 participants. The intervention group received comprehensive information and skills related to mental health literacy and parenting. Statistical analysis was conducted using SPSS software version 21, with a significance level set at 0.05. Results: Our findings revealed that the intervention group surpassed the control group in all outcome measures. Significant improvements were observed in the intervention group across all variables of interest after one and eight weeks, compared to pre-intervention levels (P<0.001). Conversely, no significant differences were noted in the control group. Conclusion: These results are promising, suggesting that programs focused on enhancing mental health literacy and parenting styles can empower mothers to play a more effective role in their children’s mental health.